Aggregation of Accounting information between differentiated accounting systems ( Case Study ) - Kdeear, Ahmed Yhia; Abdel Halim, Safwan Qusay (Journal of Economics and Administrative Sciences, 2021)
The purpose of the research is to present a proposed accounting system model for converting and aggregating accounting information within the framework of the differentiated accounting systems, and the research methodology consists of: The research problem is the existence of differentiated and dispersed accounting systems that operate within governmental economic units and at the same time seek to achieve a unified vision and goals for the organization, and the central research hypothesis is the possibility of conducting the process of conversion accounting information from the government accounting system to the unified accounting system, and then aggregate those systems. The research was conducted at the College of Administration and Economics / the University of Baghdad, and it represents a sample from a community of governmental economic units that apply different accounting systems. The research method was represented by adopting the descriptive approach in studying the problem and then diagnosing weaknesses in the accounting information within the framework of the different accounting systems. The research concluded the most important conclusions, which are that the characteristic of Faithful representation, systems theory according to accounting thought, all of them converge towards grouping in accounting practices, methods of presentation and disclosure of accounting information, as for the most critical research recommendations, they are issuing instructions from government authorities to oblige economic units that apply differentiated accounting systems to prepare their financial reports according to the proposed model